Caregiver Decision-Making for Terminally Ill Children: A Qualitative Study. Issue 3 (July 2020) - Pinto Taylor, Emily; Doolittle, Benjamin
Introduction: Many children are born with life-limiting illnesses. Medical decision-making for these children by caregivers is complex and causes significant psychosocial distress, which can be partially alleviated by effective communication with medical providers. In order for providers to support caregivers, this study explores how caregivers make decisions regarding the medical care of their terminally ill children. Methods: Semistructured interviews were conducted among caregivers of terminally ill children. Participation was voluntary and confidential. The institutional review board approved the protocol. Transcripts were read and coded by 2 authors using inductive, concurrent analysis to reach thematic saturation and generate common themes. Results: Nine interviews were completed, discussing the care of 10 children. Caregivers described decision-making as impacted by their relationships with medical providers of 2 distinct types—trusting and nontrusting. Trusting relationships were notable for a longitudinal relationship with medical staff who empowered caregivers and treated the patient primarily as a child. Nontrusting relationships were noted when the medical team objectified their child as a "patient" and appeared to withhold information. Also, nontrusting relationships occurred when caregivers felt frustration with needing to educate health-care providers about their child's illness. Conclusion: Decision-making by caregivers of terminally ill children is complex, and supporting families in this process is a critical role of all medical providers. A trusting relationship with medical team members was identified as an effective tool for well-supported decision-making, which can potentially alleviate the suffering of the child and distress of the caregivers during this emotionally charged time.